Clinical Aspects of Schizo-Obsessive Disorder - A Systematic Review - Mariana Marta da Cruz dos Santos Nobre (2021)
Objective The occurrence of OCS or OCD in the context of schizophrenia has been observed since the early 20th century. This comorbidity was proposed as a nosological entity in 1997 and has been a matter of scientific interest since then. This work aims to review clinical data available on the Schizo-Obsessive Disorder and to clarify its psychopathological importance in clinical practice using a systematic approach. Methods Research was carried out according to PRISMA guidelines in three databases - MEDLINE, Scopus and Web of Science. The references obtained were then screened and scanned for eligibility by two investigators. Risk of bias was assessed for each study with NIH tools. Results and discussion 265 references were obtained and 46 studies were included. The found prevalence of OCS and OCD in schizophrenia was 30.7% and 12.1-12.3%, respectively. Other epidemiological and clinical data was reviewed, including differential diagnosis between delusions and obsessions and the several contexts in which OCS or OCD occur in relation to schizophrenia. Conclusion Schizo-obsessive disorder is considered a clinical spectrum. OCS in schizophrenia are similar to those observed in OCD. Evidence on schizophrenia symptoms in this context is conflicting. This dimension of schizophrenia and OCS comorbidity remains controversial.